Activation of Adenosine Monophosphate-Activated Protein Kinase Drives the Aerobic Glycolysis in Hippocampus for Delaying Cognitive Decline Following Electroacupuncture Treatment in APP/PS1 Mice - Li, Jianhong; Zhang, Bingxue; Jia, Weiwei; Yang, Minguang; Zhang, Yuhao; Zhang, Jiayong; Li, Le; Jin, Tingting; Wang, Zhifu; Tao, Jing; Chen, Lidian; Liang, Shengxiang; et al. (Frontiers in Cellular Neuroscience, 2021)
Aerobic glycolysis (AG), an important pathway of glucose metabolism, is dramatically declined in Alzheimer’s disease (AD). AMP-activated protein kinase (AMPK) is a key regulator to maintain the stability of energy metabolism by promoting the process of AG and regulating glucose metabolism. Interestingly, it has been previously reported that electroacupuncture (EA) treatment can improve cognitive function in AD through the enhancement of glucose metabolism. In this study, we generated AMPK-knockdown mice to confirm the EA effect on AMPK activation and further clarify the mechanism of EA in regulating energy metabolism and improving cognitive function in APP/PS1 mice. The behavioral results showed that EA treatment can improve the learning and memory abilities in APP/PS1 mice. At the same time, the glucose metabolism in the hippocampus was increased detected by MRI-chemical exchange saturation transfer (MRI-CEST). The expression of proteins associated with AG in the hippocampus was increased simultaneously, including hexokinase II (HK2), 6-phosphofructo-2-kinase/fructose-2,6-biphosphatase 3 (PFKFB3), and pyruvate kinase M2 (PKM2). Moreover, the knockdown of AMPK attenuated AG activated by EA treatment. In conclusion, this study proves that EA can activate AMPK to enhance the process of AG in the early stage of AD.